O nexo água-energia-alimento na operação de sistemas hidrotérmicos: estudo de caso da bacia do Rio São Francisco - Deveza, Ana Carolina Peixoto (2019)
The water-energy-food nexus offers an approach that reduces trade-offs and creates synergies across the related sectors. Hydroelectricity dominates the national electricity mix. However, water is also a key resource for the agricultural sector, which in turn depends heavily on energy. This work evaluated the nexus in the scope of the operation of the National Interconnected System, having as a case study the São Francisco river basin. Through the use of three models, namely agricultural model, SMAP rainfallrunoff model and SDDP dispatch model, this work concludes that the representation of irrigation that varies with the climate, compared to the usual approach of constant seasonality, brings greater probability of economic losses for the power sector. The recent drought and water use constrain in the basin point to the need for more tools related to integrated planning to support decision making.